Assessing delivery and business models for high impact climate solutions at scale: The case of climate information services in Vietnam - Sartas, Murat; Le, Tam Thi; Nguyen, Huong Mai; Manh, Lam Tuan; Swaans, Cornelis (2024)
This report assesses optimal delivery and business models for scaling climate information solutions, specifically the Agro-Climatic Bulletin (ACB), in Vietnam. It synthesizes findings from workshops, expert feedback, and comparative analyses to provide actionable insights for decision-makers, investors, and R&D managers. The focus is on ensuring effective, sustainable, and impactful implementation of climate information services to support Vietnamese farmers.